Learning Development Athletic Kids with Media Audio Record Player for Elementary School - Muhammad Yoga Al Haj; Ega Trisna Rahayu; Resty Gustiawati; Sutirna Sutirna; Mohammad Eka Fadhilah (UNIB Press, 2024)
Education is an important component in children's lives, and elementary school is the place where the foundation of education is laid. Over the years, learning methods in Primary Schools have undergone significant development, with increasing emphasis on innovative and student-centered approaches. The use of audio record players for athletic students has many benefits. This media helps students understand the instructions given by the teacher or trainer. Clear and timely instruction is essential to ensure students can perform movements and techniques correctly. This research is categorized as research and development (R&D). Because the steps are in accordance with the research and development objectives, the ADDIE development model is used as a research and development method. The development of athletic kids learning with audio record player media has been arranged systematically according to the abilities and characteristics of elementary school students based on the results of needs analysis in the field. Therefore, learning development for athletic kids with audio record player media is very suitable for implementation in sports and health learning in elementary schools.